Long-Term Outcomes in Patients With Type 2 Myocardial Infarction and Myocardial Injury. Issue 12 (20th March 2018) - Chapman, Andrew R.; Shah, Anoop S.V.; Lee, Kuan Ken; Anand, Atul; Francis, Oliver; Adamson, Philip; McAllister, David A.; Strachan, Fiona E.; Newby, David E.; Mills, Nicholas L.
Abstract : Background: Type 2 myocardial infarction and myocardial injury are common in clinical practice, but long-term consequences are uncertain. We aimed to define long-term outcomes and explore risk stratification in patients with type 2 myocardial infarction and myocardial injury. Methods: We identified consecutive patients (n=2122) with elevated cardiac troponin I concentrations (≥0.05 µg/L) at a tertiary cardiac center. All diagnoses were adjudicated as per the universal definition of myocardial infarction. The primary outcome was all-cause death. Secondary outcomes included major adverse cardiovascular events (eg, nonfatal myocardial infarction or cardiovascular death) and noncardiovascular death. To explore competing risks, cause-specific hazard ratios were obtained using Cox regression models. Results: The adjudicated index diagnosis was type 1 or 2 myocardial infarction or myocardial injury in 1171 (55.2%), 429 (20.2%), and 522 (24.6%) patients, respectively. At 5 years, all-cause death rates were higher in those with type 2 myocardial infarction (62.5%) or myocardial injury (72.4%) compared with type 1 myocardial infarction (36.7%). The majority of excess deaths in those with type 2 myocardial infarction or myocardial injury were because of noncardiovascular causes (hazard ratio, 2.32; 95% confidence interval, 1.92–2.81 versus type 1 myocardial infarction). Despite this finding, the observed crude major adverse cardiovascular event rates were similar between groups (30.6% versus 32.6%), with differences apparent after adjustment for covariates (hazard ratio, 0.82; 95% confidence interval, 0.69–0.96). Coronary heart disease was an independent predictor of major adverse cardiovascular events in those with type 2 myocardial infarction or myocardial injury (hazard ratio, 1.71; 95% confidence interval, 1.31–2.24). Conclusions: Despite an excess in noncardiovascular death, patients with type 2 myocardial infarction or myocardial injury have a similar crude rate of major adverse cardiovascular events as those with type 1 myocardial infarction. Identifying underlying coronary heart disease in this vulnerable population may help target therapies that could modify future risk. Abstract : Supplemental Digital Content is available in the text.